The Eradication of Rampant by the Barangay Old Balara Officials Amidst General Community Quarantine: Vol. 3, No. 1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers chose to study the eradication of rampant snatching by Barangay Old Balara officials amidst the general community quarantine. This is because, since the COVID-19 pandemic, our country has suffered from myriad crises with low and irregular incomes, causing some people to lose their jobs and financial crises that have been greatly affected by the global economic crisis. These ongoing changes affect all aspects of life, and there is a particular need for research among the Barangay Old Balara as these barangays are particularly affected. In the rampant cases of snatching, it is a willful, intentional taking of something from another person with force or by a deadly weapon to scare the victim. Because of the pandemic, many people have chosen to commit this crime. When the officials of Barangay Old Balara have captured a snatcher with the help of PNP officers, they all say it is because of poverty caused by the pandemic. Many victims report incidents to the Barangay Old Balara so that the Barangay Old Balara officials, with the help of PNP officers, conduct a search operation to capture the criminals immediately. The researchers used descriptive research to validate the situation of the barangay and interviewed barangay officials and residents.